Breaking the bind: PfEMP1-specific antibodies in cerebral malaria - Banda, Josephine P.; Walker, Isobel S.; Nyirenda, Tonney; Aitken, Elizabeth H.; Rogerson, Stephen J. (Frontiers in Immunology, 2025)
Antibodies against Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) on infected erythrocytes (IEs) play a central role in naturally acquired protection against cerebral malaria (CM), yet the determinants of effective humoral immunity remain incompletely defined. We review evidence from seroepidemiological, functional, and mechanistic studies demonstrating that antibodies to endothelial protein C receptor (EPCR)‐binding cysteine-rich interdomain regions (CIDR)α1 and Duffy binding-like (DBL)β domains associated with dual EPCR and intercellular adhesion molecule 1 (ICAM1) binding correlate with reduced risk of CM, while responses to rosetting‐associated domains (DBLα, CIDRγ) and other domains are less well characterized. We synthesize findings on antibody kinetics—early, durable responses to Group A variants versus delayed, transient responses to Groups B and C—and on effector mechanisms including opsonic phagocytosis, complement activation, and Fc glycosylation. We highlight methodological challenges in measuring PfEMP1‐specific immunity, such as antigenic switching, differences between assays using single domains and native protein on IEs, and the need for physiologically relevant 3D vascular models. Finally, we identify key research priorities: mapping immunodominant epitopes across variant repertoires; longitudinal cohort studies to track antibody maturation and post‐translational modifications; and the development of broadly inhibitory monoclonal antibodies. Addressing these gaps will be critical for designing vaccines and therapeutics that harness protective antibody functions to prevent CM.